The Role of Intercultural Understanding in Enhancing International Consumer Trust: Moderated by Multilingual Branding Strategy - Mai Yuliza; Mia Muchia Desda; Tissa Aulia Damayanti; Marissa Pusparini; Roky Apriansyah; Satriadi Satriadi; Nadilla Hadring; Sri Karni (Institut Teknologi dan Bisnis Asia Malang, 2026)
The growth of the digital economy in Indonesia has created significant opportunities for international brands to expand their market share. However, the success of global brands is not only determined by product quality but also by their ability to understand local cultural values and communicate effectively in a multilingual context. This study aims to analyze the influence of intercultural understanding on international consumer trust in Indonesia. The approach used is explanatory quantitative, with a survey method involving 200 respondents who have purchased international brands in Indonesia. The data was analyzed using SEM-PLS. The results indicate that intercultural understanding has a positive and significant effect on international consumer trust. Similarly, a multilingual branding strategy has a positive effect on consumer trust. Furthermore, the moderation results indicate that a multilingual branding strategy strengthens the relationship between intercultural understanding and consumer trust. These findings confirm that a combination of cultural sensitivity and multilingual communication is a key strategy in building consumer trust and loyalty in the Indonesian market. The implications of this research demonstrate the value of cross-cultural adaptation and inclusive communication as the foundation of sustainable global marketing.